Media and Digitalization in Spatially Divergent Islands: Representing Archipelago Nature, Remoteness and Tourism Economy - Inkinen, Tommi (Springer, 2026)
This chapter deals with Turku Archipelago, its digital services, mediation, and spatiality. The case location is one of the world's largest archipelagos with approximately 20 000 islands. It is a nature tourism area motivating the chapter to examine digital tourism information services in a geographically unique and spatially divergent location. The geographical location in South-West Finland interestingly brings forth the spatial diversity in terms of physical geography as well as limited economic versatility. All these spatial characteristics affect the local digitalization potential for a naturally beautiful but economically limited location. The spatial distance measures are significantly different in absolute and relative terms in this fragmented sea area. The presents an explorative content analysis with results having implications for mediated marketing strategies and designs. Tourism information in a digital media includes a mix of public-private partnerships but also the geographical structure of cores and their vicinities (municipal divergence) having limitations with services that are provider dependent. Remotely located peripheral areas have specific needs, particularly in seasonal tourism and geographical properties requiring detailed identification in media presence and community development.
Geography's Media Turn : Exploring the Digital, Affective, and Unseen